Β-FeSi2 films prepared on 6H-SiC substrates by magnetron sputtering*Project supported by the National Natural Science Foundation of China (No. 51177134) and the Natural Science Basic Research Plan in Shaanxi Province of China (No. 2015JM6286). (June 2015) - Li, Hong; Pu, Hongbin; Zheng, Chunlei; Chen, Zhiming
Abstract β-FeSi2 thin films have been successfully prepared by magnetron sputtering and post rapid thermal annealing method on 6H-SiC (0001) substrates using a FeSi2 target and a Si target. X-ray diffraction (XRD) and Raman spectroscopy are applied to analyze the formation of β-FeSi2 films. XRD spectra reveal that the amorphous FeSi2 films are transformed to β-FeSi2 phase as the annealing temperature is increased from 500 to 900 °C for 5 min and the optimal annealing temperature is 900 °C. The formation of β-FeSi2 is also confirmed by Raman spectroscopy. Scanning electron microscope (SEM) observations indicate that the film is flat, relatively compact and the interface between β-FeSi2 and 6H-SiC is clear. Atomic force microscope (AFM) measurements demonstrate that the surface roughness confirmed by the root mean square (RMS) of the β-FeSi2 film is 0.87 nm. Near-infrared spectrophotometer observation shows that the absorption coefficient is of the order of 105 cm−1 and the optical band-gap of the β-FeSi2 film is 0.88 eV. The β-FeSi2 film with high crystal quality is fabricated by co-sputtering a FeSi2 target and a Si target for 60 min and annealing at 900 °C for 5 min.